Blockade Of PD-1 Attenuated Postsepsis Aspergillosis Via The Activation of IFN-γ and The Dampening of IL-10. Issue 4 (April 2020) - Vu, Chau Tran Bao; Thammahong, Arsa; Yagita, Hideo; Azuma, Miyuki; Hirankarn, Nattiya; Ritprajak, Patcharee; Leelahavanichkul, Asada
ABSTRACT: Background: Nosocomial aspergillosis in patients with sepsis has emerged in the past few years. Blockade of PD-1/PD-L pathway has tended to become a promising therapeutic strategy as it improved the outcome of bacterial sepsis and postsepsis secondary fungal infection. Recently, the controversial effects of PD-1 blockade on infectious diseases, including aspergillosis, have been demonstrated; therefore, the efficacy of anti-PD-1 drug still remains to be elucidated. Methods: Cecal ligation and puncture (CLP) was conducted as a mouse sepsis model. Aspergillus fumigatus spores were intravenously inoculated on day 5 post-CLP, when the immune cells succumbed to exhaustion. Amphotericin B was medicated together with or without anti-PD-1 treatment after Aspergillus infection. Results: Amphotericin B alone was not effective to treat the CLP-mice with secondary aspergillosis. In contrast, antifungal medication with the adjunctive anti-PD-1 treatment attenuated the fungal burdens in blood and internal organs, and improved the survival rate of the mice with secondary aspergillosis. These outcomes of PD-1 blockade were concurring with the enhanced CD86 expression on splenocytes, the augmented serum IFN-γ, and the dampened IL-10. Activated T cells from anti-PD-1-treated mice also highly increased IFN-γ and diminished IL-10 production. Conclusion: The blockade of PD-1 on postsepsis aspergillosis presumably reinvigorated exhausted antigen-presenting cells and T cells by upregulating CD86 expression and IFN-γ production, and dampened IL-10 production, which consequently leaded to the attenuation of secondary aspergillosis. The adjunctive anti-PD-1 therapy may become a promising strategy for the advanced immunotherapy against lethal fungal infection.